4CPS-218 Antidiabetic treatment in frail patients with type II diabetes admitted to the emergency department for altered glycaemia. (14th March 2021) - Vega-Hanna, L; Ruiz, J; Juanes-Borrego, A; Lopez-Vinardell, L; Agra-Montava, I; Mas-Malagarriga, N; Mangues-Bafalluy, MA
Abstract : Background and importance: Decompensated glycaemia is one of the main causes of emergency department (ED) visits among diabetic patients. However, information about antidiabetic treatment and risk factors associated with elderly diabetic patients revisiting the ED is scarce. Aim and objectives: To describe the oral antidiabetic treatment and glycated haemoglobin (%HbA1c) value in frail patients with type II diabetes admitted to an ED due to hyperglycaemia or hypoglycaemia and to evaluate the risk factors associated with 30 day revisits. Material and methods: This was a retrospective observational study (2017–2019). Frail patients with type II diabetes treated with oral antidiabetics admitted to an ED due to hyperglycaemia or hypoglycaemia were included. To evaluate the risk factors associated with 30 day revisits, a multivariate analysis was performed in which comorbidities and treatments risk factors with a p value <0.200 were included. Results: 48 patients were included (mean age 83 (±7.7) years); 23 (48%) were admitted for hyperglycaemia and 25 (52.1%) for hypoglycaemia. Six (12.5%) patients were being treated with insulin only, 27 (56.3%) with oral antidiabetics only and 15 (31.2%) with oral antidiabetics and insulin. The most frequent oral antidiabetic prescribed was metformin, used as monotherapy in 11 (38%) patients, combined with a sulphonylurea in 6 (20.6%) patients, with gliptins in 6 (20.6%) patients and with repaglinide in 3 (10.3%) patients. 38 (79.1%) patients presented a%Hb1Ac value during the year before the ED visit; in 11 patients (29.8%) between 7.5% and 8.5%, in 18 patients (47.3%) <7.5% and in 9 patients (23.7%) >8.5%. At discharge from the ED, treatment was modified in 14 patients (30.4%); none of them revisited the ED after 30 days. Of the 32 patients (69.6%) in whom the medication was not modified, 10 (21.7%) revisited the ED after 30 days due to alterations in glycaemia, 4 (40%) for hypoglycaemia and 6 (60%) for hyperglycaemia. In the univariate analysis, chronic heart failure and treatment modification at discharge were associated with a greater risk of 30 day revisit. In the multivariate analysis, a significant association between chronic heart failure and the risk of revisits was found (OR 4.12 (1.02–14.21)). Conclusion and relevance: Frail patients who consulted the ED for drug related problems due to antidiabetic drugs presented a high risk of revisits, with a lower risk in those patients in whom treatment was modified at ED discharge. References and/or acknowledgements: Conflict of interest: No conflict of interest